CENTROID-MOMENT TENSOR SOLUTIONS FOR APRIL JUNE, 1984 - Dziewonski, A; Franzen, J; Woodhouse, J (1985)
Centroid-moment tensor solutions are presented for 168 earthquakes that occurred during the second quarter of 1984. The solutions are obtained using corrections for aspherical Earth structure. © 1985.